Evaluation of the Implementation of the Mandalika Special Economic Zone Policy: Analysis of Policy Content, Context, and Outcomes - Khairur Raziqin; Andi Muhammad Aminullah; Muhamad Khalid Iswadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Special Economic Zone (SEZ) policy serves as a strategic government instrument to foster economic equality through large-scale investment. This study aims to evaluate the implementation of the Mandalika SEZ policy in Central Lombok Regency using the framework of policy content, context, and outcomes analysis. Employing a descriptive qualitative approach with a case study design, data were gathered through field observations, documentary studies, and in-depth interviews with key stakeholders, including bureaucrats, the management body, and local communities. The research findings reveal that in terms of content, the Mandalika SEZ policy is dominated by a macro-economic growth orientation that provides insufficient affirmative space for local economic actors. Within the context dimension, policy implementation faces challenges such as centralized governance and low meaningful community participation, complicated by international financing pressures that trigger complexities in land dispute resolution. As policy outcomes, the development of the Mandalika SEZ has successfully achieved monumental infrastructure transformation and capital inflows, yet simultaneously produced a skill gap and risks of spatial segregation for the indigenous population. This study recommends a policy reorientation toward inclusive regional development by strengthening local human resource capacity and ensuring more proportional decentralization of authority.